Born values for vector and tensor asymmetries in electron-deuteron scattering - Zhaba, V.I. (Вопросы атомной науки и техники, 2020)
Using the previously obtained analytic form factors for the deuteron wave function in the coordinate representation for the nucleon-nucleon potential Argonne v18, are calculated the Born values for vector AᴸB, AᵀB and tensor AᴸᴸB, AᵀᵀB, AᴸᵀB asymmetries, which are necessary for estimating radiative corrections to polarization observables in elastic electron-deuteron scattering in lepton variables. The momentum-angular dependence for vector and tensor asymmetries is illustrated in 3D format. Each component of the asymmetry has its own peculiarity of the form depending on the values of the scattering angle or momentum of the particle. З використанням раніше отриманих коефіцієнтів аналітичної форми хвильової функції дейтрона в координатному представленні для нуклон-нуклонного потенціалу Argonne v18 розраховані борнівські значення векторних AᴸB, AᵀB, і тензорних AᴸᴸB, AᵀᵀB, AᴸᵀB асиметрій, необхідні для оцінки радіаційних поправок до поляризаційних спостережуваних в пружному електрон-дейтронному розсіянні в лептонних змінних. Імпульсно-кутова залежність для векторних і тензорних асиметрій проілюстрована в форматі 3D. Кожна компонента асиметрії має свою особливість форми в залежності від значень кута розсіяння або імпульсу частинки. С использованием ранее полученных коэффициентов аналитической формы волновой функции дейтрона в координатном представлении для нуклон-нуклонного потенциала Argonne v18 рассчитаны борновские значения векторных AᴸB, AᵀB, и тензорных AᴸᴸB, AᵀᵀB, AᴸᵀB асимметрий, необходимые для оценки радиационных поправок к поляризационным наблюдаемым в упругом электрон-дейтронном рассеянии в лептонных переменных. Импульсно-угловая зависимость для векторных и тензорных асимметрий проиллюстрирована в формате 3D. Каждая компонента асимметрии имеет свою особенность формы в зависимости от значений угла рассеяния или импульса частицы.